HEAR THE UNHEARD VOICES OF VISUAL ART: - S.E. Dry (Acta Theologica)
The debate in contemporary visual art exhibitions focuses on the art-making process. This article aims to compare the current art-making process regarding concept development in fine arts to the concept of storytelling, as applied in narrative therapy. Several case studies done over the past three years at Tshwane University of Technology motivated the researcher to investigate this process that brought healing to many, whilst contextualising an art concept. This narrative approach in concept development is subject to the student’s ability to understand and manipulate content, together with the facilitators’ approach to the reality. The researcher proposes the use of the narrative as a starting point to identify and develop a personal theme/concept in “tracing an untold history” of “unheard voices”, not only to add content to art-making, but also to guide art students to trace their “history and meaning of a unique outcome” and rewrite their own alternative stories.